1994
DOI: 10.1080/00071669408417691
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental phytase on performance and phosphorus utilisation in broiler chickens fed a low phosphorus diet without addition of inorganic phosphates

Abstract: 1. Three experiments were conducted to evaluate the effects of the dietary addition of fungal phytase (derived from Aspergillus niger) on the performance and phosphorus utilisation in broiler chickens receiving low phosphorus diets without additional inorganic phosphates. 2. Graded amounts of supplemental phytase (125, 250, or 500 PU/kg diet) resulted in significant increases in both growth rate and food intake. However, only moderate improvements in food conversion were noted. 3. The enhancement of chick perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
48
2
8

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(71 citation statements)
references
References 3 publications
13
48
2
8
Order By: Relevance
“…Outros pesquisadores (Broz et al, 1994;Sebastian et al, 1996;Ahmad et al, 2000;Lan et al, 2002) também verificaram aumento nas cinzas ósseas das tíbias de frangos decorrente da suplementação com fitase. Denbow et al (1998) verificaram que a suplementação com fitase nos níveis de 400, 800 e 1.200 uft/kg melhorou a resistência à quebra das tíbias de frangos de corte aos 21 dias de idade.…”
Section: Resultsunclassified
“…Outros pesquisadores (Broz et al, 1994;Sebastian et al, 1996;Ahmad et al, 2000;Lan et al, 2002) também verificaram aumento nas cinzas ósseas das tíbias de frangos decorrente da suplementação com fitase. Denbow et al (1998) verificaram que a suplementação com fitase nos níveis de 400, 800 e 1.200 uft/kg melhorou a resistência à quebra das tíbias de frangos de corte aos 21 dias de idade.…”
Section: Resultsunclassified
“…Phytase supplementation to poultry and swine diets is an area of growing interest as it has the potential both to improve feed efficiency and growth rate of the animals and to decrease environmental pollution (Pen et al, 1993;Broz et al, 1994). In contrast, the other major livestock group, ruminants, requires less phosphate supplementation, possibly in part because of higher levels of phytase activity in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Further, phytate has anti-nutritive properties including formation of com-plexes with protein and divalent cations (Al-Asheh & Duvnjak, 1995). Phytases have been investigated as a possible solution to these problems, and have been reported not only to increase phosphate utilization efficiency from phytate in feeds but also to decrease phosphorus pollution (Pen et al, 1993;Broz et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The use of phytase in poultry diets has become widespread, because it reduces the P content of manure and can replace inorganic P in feed, thereby reducing P excretion and feed costs. Research on the effects of phytase in broiler diets has been extensive (Broz et al 1994;Silversides et al 2004;Selle et al 2007); research on the effects of phytase in layer diets has been less extensive (Lim et al 2003). Leske and Coon (1999) reported that commercial phytase increases the release of phytate P from various feedstuffs fed to layers and broilers between 23% and 34.9% and between 46.8% and 72.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%